2009
DOI: 10.1161/circep.108.798447
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation Ablation Strategies for Paroxysmal Patients

Abstract: No difference in terms of success rate was seen between PVAI alone and PVAI associated with defragmentation. CFAEs ablation alone had the smallest impact on AF recurrences at 1-year follow-up. These results suggest that antral isolation is sufficient to treat most patients with paroxysmal AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(88 citation statements)
references
References 19 publications
5
83
0
Order By: Relevance
“…62 Di Biase et al randomised 103 patients with paroxysmal AF to CFAE ablation, PVI, or the combination of CFAE ablation and PVI and found that freedom from atrial tachyarrhythmia at one year was present in only 23 % of patients who underwent CFAE ablation alone compared with 89 % in the PVI group, and 91 % in the CFAE plus PVI group (p<0.001 for a three-way comparison). 63 Interest thus shifted to using CFAE ablation as an adjunctive procedure during standard PVI. Elayi et al randomised 144 patients with long-standing permanent AF to circumferential pulmonary vein ablation, antral PVI or CFAE ablation followed by PVI.…”
Section: Limitations Of Targeting Rotors With Ablation For the Treatmmentioning
confidence: 99%
See 2 more Smart Citations
“…62 Di Biase et al randomised 103 patients with paroxysmal AF to CFAE ablation, PVI, or the combination of CFAE ablation and PVI and found that freedom from atrial tachyarrhythmia at one year was present in only 23 % of patients who underwent CFAE ablation alone compared with 89 % in the PVI group, and 91 % in the CFAE plus PVI group (p<0.001 for a three-way comparison). 63 Interest thus shifted to using CFAE ablation as an adjunctive procedure during standard PVI. Elayi et al randomised 144 patients with long-standing permanent AF to circumferential pulmonary vein ablation, antral PVI or CFAE ablation followed by PVI.…”
Section: Limitations Of Targeting Rotors With Ablation For the Treatmmentioning
confidence: 99%
“…65 Multiple other studies, however, have found that targeting CFAEs provided no additional freedom from AF over PVI alone even among patients with permanent AF. 57,59,60,63 A recent meta-analysis evaluated the outcomes in 622 patients across seven trials that compared PVI with PVI plus adjunctive CFAE ablation. It These studies of CFAE ablation support observations that patients with non-paroxysmal AF tend to have less success with conventional PVI alone, and they complement the previous data describing how patients with paroxysmal AF and non-paroxysmal AF appear to have variations in AF drivers.…”
Section: Limitations Of Targeting Rotors With Ablation For the Treatmmentioning
confidence: 99%
See 1 more Smart Citation
“…[19] Nevertheless, antral isolation is evidently effective to treat patients with paroxysmal AF when compared with CAFÉ defragmentation. [20] Interestingly, complex fractionations in normal atrial voltages may only represent the response of healthy atrial tissue to rapid pulmonary veins activation rather than a substrate to AF. [21] Recovery of conduction in previously ablated muscle fascicles in the antrum is a common finding in patients with recurrent AF.…”
Section: Resultsmentioning
confidence: 99%
“…90%). 1 Recent evidence suggests that complete circumferential antral ablation is not even necessary for PV isolation. 2 When AF persists beyond one week, electrical and anatomic substrate remodeling typically occurs.…”
Section: Introductionmentioning
confidence: 99%